The Anatomy of the Aging Face: A Review - Cotofana, Sebastian; Fratila, Alina A. M.; Schenck, Thilo L.; Redka-Swoboda, Wolfgang; Zilinsky, Isaac; Pavicic, Tatjana (Facial Plastic Surgery, 2016)
Rejuvenative procedures of the face are increasing in numbers, and a plethora of different therapeutic options are available today. Every procedure should aim for the patient's safety first and then for natural and long-lasting results. The face is one of the most complex regions in the human body and research continuously reveals new insights into the complex interplay of the different participating structures. Bone, ligaments, muscles, fat, and skin are the key players in the layered arrangement of the face.Aging occurs in all involved facial structures but the onset and the speed of age-related changes differ between each specific structure, between each individual, and between different ethnic groups. Therefore, knowledge of age-related anatomy is crucial for a physician's work when trying to restore a youthful face.This review focuses on the current understanding of the anatomy of the human face and tries to elucidate the morphological changes during aging of bone, ligaments, muscles, and fat, and their role in rejuvenative procedures.
Keywords: facial bones; fat compartments; facial muscles; facial ligaments; aging